2017
DOI: 10.1177/1049732317739611
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Uses of Public and Private Health Care in a Brazilian Favela

Abstract: Since 1988, Brazil has reorganized and expanded its public health care system, defining access to health care as a right of every citizen. In parallel, the private health care sector grew rapidly to become one of the largest in the world. We explore the use of public and private health care by a low-income population living in a favela, Rio das Pedras, in Rio de Janeiro. At the time of data collection, only part of the community was covered by the primary health care program. We conducted semistructured interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
3
11
0
1
Order By: Relevance
“…This is consistent with findings of another study where these states reportedly have poor quality health services and inadequate specialty services (Bajpai, 2014). A study done in Rio de Janeiro showed that participants sought health care in the private sector because they perceived it as an assurance of receiving the required treatment and because of the feeling of disempowerment they felt in their interactions with doctors in the public health system (Castiglione et al, 2018). Tertiary health facilities were set up in the last decade to meet the shortfall of quality health services ("Bill on AIIMS-Like Institutes Introduced in Lok Sabha," 2012) but have not bridged service gaps, as seen in our analysis.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This is consistent with findings of another study where these states reportedly have poor quality health services and inadequate specialty services (Bajpai, 2014). A study done in Rio de Janeiro showed that participants sought health care in the private sector because they perceived it as an assurance of receiving the required treatment and because of the feeling of disempowerment they felt in their interactions with doctors in the public health system (Castiglione et al, 2018). Tertiary health facilities were set up in the last decade to meet the shortfall of quality health services ("Bill on AIIMS-Like Institutes Introduced in Lok Sabha," 2012) but have not bridged service gaps, as seen in our analysis.…”
Section: Discussionsupporting
confidence: 86%
“…This study highlighted issues of access such as the routine problem of long queues, also seen in another study in a slum settlement in Delhi (Barua & Pandav, 2011). Another study done in Rio de Janeiro showed that the even while appointments were scheduled weeks in advance, the doctor was absent on the day of the appointment (Castiglione et al, 2018).…”
Section: Discussionsupporting
confidence: 54%
“…This underlines the importance of achieving and maintaining political support for investment in PHC, including embracing a model of universal provision around which popular support can be built—especially during periods when public expenditures are severely constrained. Other studies of PHC in Rio de Janeiro have identified long distances to clinics, wait times, staff and equipment shortages, and perceived poor treatment by healthcare professionals as barriers to accessing healthcare, and addressing these is essential to ensure investments in PHC that characterized the program in Rio de Janeiro are sustained [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of resources impedes the access to public healthcare [33,34], and the perceived quality of service is higher in the private sector. This influences Brazilian's health seeking behavior, even in poor urban settings [35].…”
Section: Dengue Surveillance In Brazilmentioning
confidence: 99%